Globalization : a short history - Osterhammel, Jürgen (Princeton University Press, 2005)
"Arguing that the world did not turn "global" overnight, the book traces the emergence of globalization over the past seven or eight centuries. In fact, the authors write, the phenomenon can be traced back to early modern large-scale trading, for example, the silk trade between China and the Mediterranean region, the shipping routes between the Arabian Peninsula and India, and the more frequently traveled caravan routes of the Near East and North Africa - all conduits for people, goods, coins, artwork, and ideas." "Osterhammel and Petersson argue that the period from 1750 to 1880 - an era characterized by the development of free trade and the long-distance impact of the industrial revolution - represented an important phase in the globalization phenomenon." "This book will appeal to historians, economists, and anyone in the social sciences who is interested in the historical emergence of globalization."--Jacket.